2006
DOI: 10.3998/ark.5550190.0008.b02
|View full text |Cite
|
Sign up to set email alerts
|

ortho-Quinone amines and derivatives: the influence of structure on the rates and modes of intramolecular reaction

Abstract: The influence of N-substituents and chain length on the mode and rate of intramolecular reaction of ortho-quinone amines is reviewed. These reactions have been the subject of a series of studies over the last decade using a combination of pulse radiolysis, enzyme oximetry and preparative chemistry. Alternative reactions are cyclisation, spirocyclisation and para-quinomethane formation. The observed mode of reaction is determined by both the length of the ortho-quinone side chain and the nature of the N-substit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Around 50% HCA was left in the hydrogel after 2 h. This difference in the release profile may be due to the difference in ionization status of the catechol compounds. DA and DOPA are cationic, while HCA is anionic at pH 5.5. , Therefore, only HCA can interact electrostatically with the positively charged CH at pH 5.5. Such electrostatic interactions are responsible for the slower release of HCA.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Around 50% HCA was left in the hydrogel after 2 h. This difference in the release profile may be due to the difference in ionization status of the catechol compounds. DA and DOPA are cationic, while HCA is anionic at pH 5.5. , Therefore, only HCA can interact electrostatically with the positively charged CH at pH 5.5. Such electrostatic interactions are responsible for the slower release of HCA.…”
Section: Resultsmentioning
confidence: 99%
“…DA and DOPA are cationic, while HCA is anionic at pH 5.5. 41,42 Therefore, only HCA can interact electrostatically with the positively charged CH at pH 5.5. Such electrostatic interactions are responsible for the slower release of HCA.…”
Section: ■ Introductionmentioning
confidence: 99%
“…However, it is possible that the relative stability of the intermediate quinones generated on the CD-melanin surface also plays a role, in accord with the faster intramolecular cyclization rate constants reported for DOPA quinone (k = 3.8 s À1 at pH 7.4) versus NE quinone (k = 0.37 s À1 at pH 7.0) and DA quinone (k = 0.04 s À1 at pH 7.0). 11 Rate acceleration varied in a non-linear manner with the amount of CD-melanin (Fig. 2, panel b), reflecting likely non-linear changes in the total surface area of the heterogeneous redox system with concentration, due to aggregation phenomena.…”
mentioning
confidence: 99%
“…We have previously described investigations of the reactions of a variety of dopamine ortho-quinone derivatives 4. 1,2 In these studies we have generated the ortho-quinones 4 by (i) tyrosinase oxidation of phenols 1 or catechols 2, 3-7 (ii) pulse radiolytic oxidation of catechols 2, 3-6,8 and (iii) chemical oxidation of catechols 2. [9][10][11] We have found that cyclisation to the 5-position to give the bicyclic products 5 (Scheme 1) is usually fast but that faster transient formation of the less stable spirocyclic compounds 3 is sometimes observed.…”
Section: Introductionmentioning
confidence: 99%